Light behind the curtain: photoregulation of nuclear architecture and chromatin dynamics in plants - Perrella, Giorgio (New Phytol, 2016)
Light is a powerful stimulus regulating many aspects of plant development and phenotypic plasticity. Plants sense light through the action of specialized photoreceptor protein families that absorb different wavelengths and intensities of light. Recent discoveries in the area of photobiology have uncovered photoreversible changes in nuclear organization correlated with transcriptional regulation patterns that lead to de‐etiolation and photoacclimation. Novel signalling components bridging photoreceptor activation with chromatin remodelling and regulation of gene expression have been discovered. Moreover, coregulated gene loci have been shown to relocate to the nuclear periphery in response to light. The study of photoinduced changes in nuclear architecture is a flourishing area leading to major discoveries that will allow us to better understand how highly conserved mechanisms underlying genomic reprogramming are triggered by environmental and endogenous stimuli. This review aims to discuss fundamental and innovative reports demonstrating how light triggers changes in chromatin and nuclear architecture during photomorphogenesis.